Coordination behavior of three geometric isomers of indole-based s-benzyldithiocarbazone ligands towards nickel, zinc and cadmium divalent ions - Khaledi, H.; Olmstead, M.M.; Ali, Hapipah Mohd (2011)
Three indolyl-imine ligands have been synthesized through the condensation of S-benzyldithiocarbazate with indole-2-carbaldehyde, indole-3-carbaldehyde and indole-7-carbaldehyde. Treatment of these Schiff bases with acetate salts of Ni(II), Zn(II) and Cd(II) in ethanol yielded a series of complexes of 2:1 type (ligand/metal ratio) in which the ligands coordinated to the metal ions as monoanionic NS bidentate chelates. While the 2-imineindole and 3-imineindole formed the expected five-membered chelate rings, the X-ray crystal structure of [Cd(HL3)(py)(2)], (HL3 = the mono-deprotonated 7-imineindole), revealed an unusual mode of coordination, namely formation of four-membered rings with the metal atom. Reaction of the 7-imineindole with the metal ions in the presence of potassium hydroxide produced complexes of the type [M(L-3)(H2O)] in which the Schiff base acts as a dianionic NNS tridentate ligand. (C) 2010 Elsevier B.V. All rights reserved.